Kepemimpian Situasional dalam Pendidikan Islam - Nur Khoironi; Abdulloh Hamid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The situational approach as an approach toward the leadership requires that a leader must be understand with the behavior, nature and character of his subordinates, and the situation before using a certain style or type of leadership. This approach requires leaders to have the ability to diagnose human behavior. The success of a leader according to situational theory is determined by the characteristics of leadership with certain behaviors that are adjusted to the demands of the leadership situation and organizational situations faced by accounting the factors of space and time.